Production of Synthetic Seed in Cassava ( Manihot esculenta Crantz) - Hegde, Vivek; Makeshkumar, T; Sheela, M N; Chandra, C Visalakshi; Koundinya, A V V; Anil, Shirly Raichal; Muthuraj, R; Darshan, S (JOURNAL OF ROOT CROPS, 2017)
Cassava is an important source of energy in the diet of most tropical countries of the world. It has enormous potential in India for food security and industrial uses due to its ability to grow in marginal and waste lands where other crops could not survive. Commercial planting of cassava is done from stem cuttings and because of the low multiplication rate, bulkiness of seed material and difficulty in transporting the planting materials to distant places, the crop could not make much impact either as food crop or industrial crop in the country. These limitations can be overcome by the development of synthetic seed technology. Synthetic seeds have multiple advantages including mass propagation of elite plant, ease of handling, long-term storage and low cost of production. In this study, different concentrations of sodium alginate and calcium chloride solutions were tested in order to optimize the shape, texture and germination frequency of synthetic seeds of cassava. The nodes containing axillary buds from in vitro grown cassava variety, H-226 were encapsulated with 2%, 3% and 4% sodium alginate (w/v) along with Murashige and Skoog (MS) salts without calcium salt and exposed to 75mM, 100mM and 125 mM calcium chloride solution (CaCl2.2H2O). Round and sufficiently hard beads/synthetic seeds were observed by the encapsulation with sodium alginate 3% and exposed to 100 mM CaCl2.2H2O combination. It showed that encapsulation at 2% and 3% sodium alginate concentrations and exposed to CaCl2.2H2O at 75mM and 100mM concentrations, gave high germination frequency under in vitro condition. The synthetic seeds have the possibility of being an efficient way for germplasm storage, exchange and propagation of pathogen-free planting material